Complement Factor I Variants in Complement-Mediated Renal Diseases - Zhang, Yuzhou; Goodfellow, Renee X.; Ghiringhelli Borsa, Nicolo; Dunlop, Hannah C.; Presti, Stephen A.; Meyer, Nicole C.; Shao, Dingwu; Roberts, Sarah M.; Jones, Michael B.; Pitcher, Gabriella R.; Taylor, Amanda O.; Nester, Carla M.; et al. (Frontiers in Immunology, 2022)
C3 glomerulopathy (C3G) and atypical hemolytic uremic syndrome (aHUS) are two rare diseases caused by dysregulated activity of the alternative pathway of complement secondary to the presence of genetic and/or acquired factors. Complement factor I (FI) is a serine protease that downregulates complement activity in the fluid phase and/or on cell surfaces in conjunction with one of its cofactors, factor H (FH), complement receptor 1 (CR1/CD35), C4 binding protein (C4BP) or membrane cofactor protein (MCP/CD46). Because altered FI activity is causally related to the pathogenesis of C3G and aHUS, we sought to test functional activity of select CFI missense variants in these two patient cohorts. We identified 65 patients (16, C3G; 48, aHUS; 1 with both) with at least one rare variant in CFI (defined as a MAF <0.1%). Eight C3G and eleven aHUS patients also carried rare variants in either another complement gene, ADAMTS13 or THBD. We performed comprehensive complement analyses including biomarker profiling, pathway activity and autoantibody testing, and developed a novel FI functional assay, which we completed on 40 patients. Seventy-eight percent of rare CFI variants (31/40) were associated with FI protein levels below the 25th percentile; in 22 cases, FI levels were below the lower limit of normal (type 1 variants). Of the remaining nine variants, which associated with normal FI levels, two variants reduced FI activity (type 2 variants). No patients carried currently known autoantibodies (including FH autoantibodies and nephritic factors). We noted that while rare variants in CFI predispose to complement-mediated diseases, phenotypes are strongly contingent on the associated genetic background. As a general rule, in isolation, a rare CFI variant most frequently leads to aHUS, with the co-inheritance of a CD46 loss-of-function variant driving the onset of aHUS to the younger age group. In comparison, co-inheritance of a gain-of-function variant in C3 alters the phenotype to C3G. Defects in CFH (variants or fusion genes) are seen with both C3G and aHUS. This variability underscores the complexity and multifactorial nature of these two complement-mediated renal diseases.